Answer:
Give him brainliest
Step-by-step explanation:
The answer is the letter A! I hope this helps
Answer:
y = 2x - 1
Step-by-step explanation:
Note the difference between consecutive terms of y are constant, that is
1 - (- 1) = 3 - 1 = 5 - 3 = 7 - 5 = 9 - 7 = 2
Thus the equation is of the form y = 2x ± c ← c is a constant
Substitute values of x to determine the required value of c
x = 0 : 2 × 0 = 0 ← require to subtract 1 for y = - 1
x = 1 : 2 × 1 = 2 ← require to subtract 1 for y = 1
x = 2 : 2 × 2 = 4 ← require to subtract 1 for y = 3, and so on
Thus the required equation is
y = 2x - 1
Answer:
switch your 5 and 6
Step-by-step explanation:
I think the equation would be
53x5=265
also not to be that person, but its *times
Answer:
35
Step-by-step explanation:
you add it all up 17+12 29 then you add 29+6 and that equals 35